A Highly Sensitive Narrowband Nanocomposite Photodetector with Gain. Issue 10 (18th January 2016) - Shen, Liang; Fang, Yanjun; Wei, Haotong; Yuan, Yongbo; Huang, Jinsong
Abstract : A narrowband red‐light nanocomposite photodetector with gain is presented based on the polymer and fullerene derivative incorporating inorganic quantum dots. The introduced trap‐induced hole injection dramatically improves the specific detectivity by 20‐fold. A remarkable achievement is obtained with simultaneously increased linear dynamic range to 110 dB and improved noise equivalent power to 5 pW cm −2 .